Using Fictional Medical Television Programs to Teach Interprofessional Communication to Graduating Fourth-Year Medical Students. Issue 12 (December 2022) - Hoffman, Beth L.; Wolynn, Riley; Sidani, Jaime E.; Donovan, Anna K.
Abstract : Previous research suggests that fictional medical television programs (eg, ER ) may be an innovative avenue through which to teach medical students interprofessional communication skills, which are crucial to high-quality patient care. This article provides an overview of the authors' development and evaluation of a workshop for graduating fourth-year medical students that used clips from medical television shows. Results suggest the workshop is acceptable to students and may be efficacious at improving their interprofessional communication skills and attitudes toward communication skills training. Abstract: Objectives: Effective interprofessional (IP) communication is crucial to high-quality patient care, but significant obstacles remain regarding implementing IP communication curricula for undergraduate medical students. As such, as part of a bootcamp required for University of Pittsburgh graduating medical students in 2021, we developed and evaluated a workshop using clips from medical television shows (eg, ER ) to teach IP communication skills. Methods: The workshop was hosted on Zoom videoconferencing software and evaluated using pre- and postcurricular surveys that included adapted Communication Skills Attitude Scale (CSAS) and Student Perceptions of Interprofessional Clinical Education-Revised (SPICE-R) instruments. The postcurricular survey also included two open-ended items. We used Wilcoxon signed-rank tests to compare pre- and postcurricular CSAS and SPICE-R scores and used thematic analysis for qualitative data. Results: Approximately 94% (n = 105) of assigned students attended the workshop. Comparison of pre- and postcurricular means for all CSAS and SPICE-R items indicated improvements in attitudes toward communication training and IP communication, with statistically significant ( P < 0.05) changes for 4 of 10 (40%) CSAS items and 8 of 10 (80%) SPICE-R items. Thematic analysis of open-ended items suggests that the workshop is acceptable to students and may be efficacious at improving both their IP communication skills and skills related to addressing equity and bias. Conclusions: Results suggest that using clips from fictional medical television programs may be a valuable approach to teaching graduating medical students IP communication skills. Future research could examine whether improved attitudes are sustained over time and the influence of the workshop on clinical IP communication behavior.